2018
DOI: 10.2215/cjn.12991117
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids in the Treatment of Glomerular Diseases

Abstract: Glucocorticoids exert anti-inflammatory and immunosuppressive activities by genomic and nongenomic effects. The classic genomic effects are mediated by cytosolic glucocorticoid receptors that can upregulate the expression of anti-inflammatory proteins in the nucleus (transactivation) or repress the translocation of proinflammatory transcription factors from the cytosol into the nucleus (transrepression). The nongenomic effects are probably mediated by membrane glucocorticoid receptors. Glucocorticoid receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 50 publications
0
51
0
Order By: Relevance
“…A large randomized controlled trial showed that dexamethasone reduced 28-day mortality in severely ill patients who were receiving either invasive mechanical ventilation or oxygen alone at randomization, but not among those receiving no respiratory support 216 . These findings are encouraging since dexamethasone treatment is also highly beneficial in patients with pre-existing chronic kidney disease 217 , 218 .…”
Section: Therapeutic Considerationsmentioning
confidence: 78%
“…A large randomized controlled trial showed that dexamethasone reduced 28-day mortality in severely ill patients who were receiving either invasive mechanical ventilation or oxygen alone at randomization, but not among those receiving no respiratory support 216 . These findings are encouraging since dexamethasone treatment is also highly beneficial in patients with pre-existing chronic kidney disease 217 , 218 .…”
Section: Therapeutic Considerationsmentioning
confidence: 78%
“…Glucocorticoids have been extensively used in the treatment of immune-related kidney diseases because of their anti-inflammatory and immunosuppressive effects 1 . However, the use of systemic glucocorticoids is associated with a range of adverse effects, including increased risks of osteoporosis and fracture 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Using the validated gene set for further analyses, a convergence of molecular mechanisms was identified including activation of inflammatory pathways and suppression or inhibition of differentiation related pathways. For the inflammatory-related pathways, evidence for their potential causal role in autoimmune or renal disease has been established, including TNF [28][29][30] , JAK-STAT 16 , NFÎșB 31 , proteasome signaling 32,33 , and reactivation of glucocorticoid signaling through the use of glucocorticoid agonists 34 . JAK-STAT pathway activation has already been implicated across other kidney diseases including diabetic kidney disease (DKD) [35][36][37][38] , and FSGS 13 .…”
Section: Discussionmentioning
confidence: 99%